INFLEKSI VERBA DASAR BERPOLA FA‘ALA-YAF‘ULU DALAM KAMUS AL-MUNAWWIR ARAB-INDONESIA: TINJAUAN MORFOLOGI - Fathiyaturrohmah, Tri Yanti Nurul Hidayati (Arabic Literature Department, 2016)
The changing process of word occured in three forms : the basic forms , the lexical identity , and the word category status. The process that resulted other forms of the word with sama lexical identity is caled by flexion and inflexion , or at-tashrif in arabic term. There are supporting processes in the changing of Arabic verb such as i‘lal (vocalization), idgham (elipsis), dan ibdal (mutation). The research explains about changing of the basic verbs of form patterned faala–yaf'ulu in inflection in al-Munawwir Arabic-Indonesia dictionary. The providing of data in this research through observation by using languages of basic trilitteral verbs in al-Munawwir Arabic-Indonesia dictionary is using taking apart as basic technique, and noted as advanced techniques. Distributional methods were used to analyze the data, by using the technique for direct items as the basic techniques, as well as the technique of disappeared and change as advanced technique. The result of the basic verb inflection patterned fa'ala-yaf'ulu in al-Munawwir ArabicIndonesia dictionary itheproces of changing the form of verbs in fa'ala-yaf'ulu patterned inflection is i‘lal